A double-layered anti-cutting fabric, its preparation method and application

CN122879989APending Publication Date: 2026-10-09SWOTO PROTECTION & TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611261924.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

本申请提供的抗切割面料在保持纤维原有高强度与优异抗切割性能的同时,能够与水性聚氨酯胶膜持久稳定的界面化学键合,不易剥落,且所用改性水性聚氨酯双模树脂兼具高交联密度、高韧性和高强度,使面料在受力时能够实现应力在纤维与树脂之间的高效传递与能量耗散,进而使面料具有优异的抗切割性能、高断裂强力和高撕破强力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of textiles and relates to a double-layer anti-cutting fabric and a preparation method and application thereof. The anti-cutting fabric comprises a grey cloth and a water-based polyurethane adhesive film coated on the surface of the grey cloth. The grey cloth comprises a surface layer and an inner layer. The surface layer and the inner layer are connected through connecting warp yarns. The warp yarns of the surface layer and the inner layer are modified ultra-high molecular weight polyethylene fibers. The weft yarns of the surface layer and the inner layer are modified aramid fibers. The material of the water-based polyurethane adhesive film comprises modified water-based polyurethane double-mode resin. The anti-cutting fabric can realize efficient transmission of stress and energy dissipation between fibers and resin when stressed, so that the fabric has excellent anti-cutting performance, high breaking strength and high tear strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of textile technology and relates to a double-layered cut-resistant fabric, its preparation method and application. Background Technology

[0002] In high-risk work environments, such as police protection, emergency rescue, machining, and high-end sports, protection against mechanical injuries to the human body remains a key focus of industrial textile research and development. Cut-resistant and puncture-resistant fabrics, as core materials for personal protective equipment, directly impact user safety. High-density double-layer fabrics, due to their advantages in structural density, interlayer bonding strength, and functional designability, have become an important development direction for such protective fabrics. These fabrics typically employ two or more high-performance fibers combined with a specific double-layer fabric structure design to effectively resist cuts, scratches, and punctures from sharp objects.

[0003] Currently, ultra-high molecular weight polyethylene (UHMWPE) fiber and aramid fiber are two mainstream materials for preparing high-performance cut-resistant fabrics. UHMWPE fiber is renowned for its extremely high specific strength and specific modulus, but due to its highly crystalline surface, lack of polar groups, and strong chemical inertness, its interfacial bonding strength with the resin matrix is ​​extremely low. Under stress, the fiber is prone to interfacial debonding failure, failing to fully utilize its high strength and high modulus characteristics. Although existing technologies often employ plasma treatment or chemical reagent treatment to improve its surface activity, these methods have significant limitations: on the one hand, activated surface polar groups are prone to relaxation or migration, leading to a decay of treatment effect over time and uneven grafting rates; on the other hand, excessive surface treatment often damages the fiber itself, resulting in decreased strength and making it difficult to maintain the fiber's original excellent cut-resistant properties while achieving durable and stable interfacial chemical bonding.

[0004] Aramid fibers also face the challenge of surface modification. Their smooth surface, lack of active groups, and similar to ultraviolet (UHMW) fibers, extreme sensitivity to ultraviolet (UV) light, lead to photo-oxidative degradation of the aramid fiber molecular chains under prolonged UV exposure. This results in a significant decrease in strength retention, severely impacting the lifespan of protective equipment. Existing surface treatment technologies, such as strong acid etching or plasma radiation, while improving surface roughness to some extent, easily damage the fiber's intrinsic structure, causing irreversible loss of mechanical properties. Furthermore, a single resin coating layer lacking chemical cross-linking and anchoring to the fiber surface results in insufficient interfacial bonding between the coating and the fiber, making it prone to peeling under external forces and failing to provide durable protection.

[0005] Regarding the resin matrix, conventional waterborne polyurethane (PU) resins, due to their linear molecular chain structure and lack of effective crosslinking branching points, suffer from low crosslinking density, insufficient mechanical strength, and poor water resistance after curing. Existing resin modification methods mostly employ single crosslinking systems or simple physical blending, making it difficult to construct a high-density interpenetrating network structure within the resin. This directly results in insufficient toughness and poor impact resistance of the resin film, failing to achieve a good synergistic effect with high-strength fiber reinforcements. Under dynamic impact loads, microcracks are easily generated and rapidly propagate.

[0006] To address the inherent defects of the aforementioned fiber and resin matrix, some improvement solutions have been attempted in the prior art. For example, CN116254706A discloses a puncture-resistant fabric for fencing uniforms and its preparation method. This fabric includes a base fabric layer, a puncture-resistant layer, and a coating layer. The puncture-resistant layer is a blend of ultra-high molecular weight polyethylene fiber, polyetheretherketone fiber, and aramid fiber. The coating layer is made from epoxy resin, thermoplastic polyurethane, diethylaminopropylamine, modified inorganic fibers, and other raw materials. This patent achieves a certain degree of puncture resistance by physically blending ultra-high molecular weight polyethylene fiber and aramid fiber, and then applying a resin coating layer. However, this technical solution has the following shortcomings: Ultra-high molecular weight polyethylene fibers have highly crystalline surfaces, lack polar groups, and are extremely chemically inert; aramid fibers have smooth surfaces and lack active groups. The interfacial wettability between these fibers and the epoxy resin and thermoplastic polyurethane coating layers is extremely poor. Physical blending and simple coating alone cannot form a strong chemical bond between the fiber and the resin. Under stress, the fiber is easily pulled out or slips from the resin matrix, leading to interfacial debonding failure. Furthermore, this technical solution does not perform anti-UV aging treatment on the aramid fibers. Aramid fibers are extremely sensitive to UV light, and long-term exposure severely reduces their strength retention, affecting the fabric's durable protective performance. In addition, the coating resin used is a physical blend of epoxy resin and thermoplastic polyurethane. The resin molecular chains have a linear structure, lack cross-linking points, have low cross-linking density, and insufficient film toughness. Under dynamic impact loads, microcracks easily form and propagate rapidly, failing to form an effective stress transfer and synergistic energy dissipation mechanism with the fiber reinforcement, resulting in poor cut resistance of the fabric.

[0007] Therefore, there is an urgent need to develop a double-layer fabric that can overcome the problems of poor bonding between the fiber and resin interface and insufficient resin matrix properties, and thus have excellent cut resistance. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the purpose of this application is to provide a double-layered cut-resistant fabric, its preparation method, and its application. In the double-layered cut-resistant fabric, the fibers and resin matrix have high-strength chemical bonds, and the polyurethane resin used has high strength and high toughness, thereby giving the fabric excellent cut resistance, high breaking strength, and high tear strength.

[0009] To achieve this objective, the present application adopts the following technical solution: In a first aspect, this application provides a double-layered cut-resistant fabric, the cut-resistant fabric comprising a greige fabric and an aqueous polyurethane film covering the surface of the greige fabric; The fabric includes a surface layer and an inner layer, which are connected by splicing warp yarns. The warp yarns of the outer and inner layers are all modified ultra-high molecular weight polyethylene fibers, and the weft yarns of the outer and inner layers are all modified aramid fibers. The material of the waterborne polyurethane film includes a modified waterborne polyurethane dual-mode resin.

[0010] The cut-resistant fabric provided in this application maintains the original high strength and excellent cut resistance of the fiber while being able to form a long-lasting and stable interfacial chemical bond with the waterborne polyurethane film, making it difficult to peel off. Furthermore, the modified waterborne polyurethane bimodal resin used has high crosslinking density, high toughness, and high strength, enabling the fabric to achieve efficient stress transfer and energy dissipation between the fiber and the resin when under stress. This results in the fabric having excellent cut resistance, high tensile strength, and high tear strength.

[0011] In some specific embodiments, the modified ultra-high molecular weight polyethylene fiber is obtained by plasma activation, acrylamide graft copolymerization, and polydopamine-chitosan composite coating construction of ultra-high molecular weight polyethylene fiber.

[0012] In this application, the modified ultra-high molecular weight polyethylene fiber is activated by plasma at 20~40℃ (e.g., 22℃, 24℃, 26℃, 28℃, 30℃, 32℃, 34℃, 36℃, or 38℃, etc.), which introduces active reactive groups on the fiber surface. Then, through acrylamide graft copolymerization, polar amide groups are fixed on the fiber surface through covalent bonds, giving the fiber lasting hydrophilicity and reactivity, solving the problem of unstable grafting rate caused by the decay of active groups over time in conventional plasma treatment. Finally, an antibacterial hydrophilic surface layer is constructed on the fiber surface through dopamine auto-oxidation polymerization and chitosan Schiff base reaction, making the fiber surface change from inert to active, from hydrophobic to hydrophilic, and from having no reactive sites to being rich in chemical bonding sites. The above three surface treatments work together to enable the modified fiber to achieve high-strength interfacial chemical bonding with the resin matrix without damaging the bulk strength, solving the problem that ultra-high molecular weight polyethylene fiber cannot form a strong interfacial bond with the resin matrix due to its extremely inert surface.

[0013] In some specific embodiments, the modified ultra-high molecular weight polyethylene fiber is prepared by the following method, which includes the following steps: (A1) Ultra-high molecular weight polyethylene fibers were subjected to plasma surface activation treatment in a mixed atmosphere of oxygen and argon to obtain surface-activated ultra-high molecular weight polyethylene fibers. (A2) The surface-activated ultra-high molecular weight polyethylene fiber obtained in step (A1) is immersed in an aqueous solution of acrylamide to carry out a copolymerization reaction, and amide polar groups are introduced on the surface of the ultra-high molecular weight polyethylene fiber to obtain ultra-high molecular weight polyethylene fiber grafted copolymerized with acrylamide. (A3) The acrylamide graft copolymerized ultra-high molecular weight polyethylene fiber obtained in step (A2) is immersed in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride and chitosan to carry out the reaction. Through the self-oxidative polymerization of dopamine and the Schiff base reaction of chitosan, a polydopamine-chitosan composite coating is formed on the fiber surface, thus obtaining the modified ultra-high molecular weight polyethylene fiber.

[0014] In some specific embodiments, the temperature of the plasma surface activation treatment in step (A1) is 20~40℃, such as 22℃, 24℃, 26℃, 28℃, 30℃, 32℃, 34℃, 36℃ or 38℃.

[0015] In some specific embodiments, the power of the plasma surface activation treatment in step (A1) is 150~250W (e.g., 150 W, 170 W, 190 W, 210 W, 230 W or 250 W, etc.), and the time is 4~8 min (e.g., 4 min, 5 min, 6 min, 7 min or 8 min, etc.).

[0016] In some specific embodiments, the linear density of the ultra-high molecular weight polyethylene fiber in step (A1) is 150~400 dtex, such as 1700 dtex, 200 dtex, 220 dtex, 240 dtex, 260 dtex, 280 dtex, 300 dtex, 320 dtex, 340 dtex, 360 dtex or 380 dtex, etc.

[0017] In some specific embodiments, the acrylamide in the acrylamide aqueous solution in step (A2) has a mass percentage content of 5-10%, such as 5%, 6%, 7%, 8%, 9% or 10%.

[0018] In some specific embodiments, the amount of acrylamide aqueous solution used in step (A2) is 8 to 15% of the mass of ultra-high molecular weight polyethylene fiber, such as 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0019] In some specific embodiments, the temperature of the copolymerization reaction in step (A2) is 35~50°C (e.g., 35°C, 37°C, 39°C, 42°C, 45°C, 48°C or 50°C, etc.), and the time is 1~3 h (e.g., 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc.).

[0020] In some specific embodiments, the molar concentration of the tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution in step (A3) is 0.06~0.1 mol / L (e.g., 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L, etc.), and the pH value is 8~9 (e.g., 8, 8.2, 8.4, 8.6, 8.8 or 9, etc.).

[0021] In some specific embodiments, based on the amount of the tris(hydroxymethyl)aminomethane hydrochloride buffer solution used in step (A3) being 100%, the amount of dopamine hydrochloride is 1-3% (e.g., 1%, 1.5%, 2%, 2.5% or 3%), and the amount of chitosan is 1-2% (e.g., 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%).

[0022] In some specific embodiments, the amount of dopamine hydrochloride added in step (A3) is 3 to 5% of the mass of ultra-high molecular weight polyethylene fiber, such as 3%, 3.5%, 4%, 4.5% or 5%.

[0023] In some specific embodiments, the amount of chitosan added in step (A3) is 1 to 3% of the mass of ultra-high molecular weight polyethylene fiber, such as 1%, 1.5%, 2%, 2.5% or 3%.

[0024] In some specific embodiments, the temperature of the reaction in step (A3) is 20~40°C (e.g., 20°C, 25°C, 30°C, 35°C or 40°C, etc.), and the time is 12~24 h (e.g., 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h, etc.).

[0025] In some specific embodiments, the modified aramid fiber is prepared by coating aramid fiber with dopamine hydrochloride self-polymerization, depositing nano-titanium dioxide sol-gel, and cross-linking and reinforcement treatment with amino-terminated hyperbranched polyamide.

[0026] In this application, the modified aramid fiber is coated onto the fiber surface via polydopamine hydrochloride self-polymerization, introducing a large number of phenolic hydroxyl and amino active groups, thus solving the problem of smooth aramid fiber surfaces lacking active sites. Then, a nano-titanium dioxide sol-gel deposition process is used to form a nano-titanium dioxide particle layer on the polydopamine layer surface. Utilizing the strong absorption and scattering properties of nano-titanium dioxide for ultraviolet light, the aramid fiber is endowed with excellent anti-UV aging properties, overcoming the problem of unmodified aramid fiber's sensitivity to ultraviolet light and its rapid strength decay after long-term exposure. Finally, it is reinforced by end-amino hyperbranched polyamide crosslinking. Multiple chemically bonded crosslinking structures are formed between the end-amino groups and the hydroxyl groups on the nano-titanium dioxide surface and the phenolic hydroxyl groups of the polydopamine layer, firmly anchoring the functional coating to the aramid fiber body through covalent bonds, solving the durability problem of conventional surface treatment coatings easily peeling off due to a lack of chemical crosslinking anchoring. In some specific embodiments, the modified aramid fiber is prepared by the following method, which includes the following steps: (B1) Aramid fibers are immersed in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride to react and obtain aramid fibers with dopamine hydrochloride self-polymerized surface coating. (B2) The aramid fibers coated with dopamine hydrochloride obtained in step (B1) were immersed in an aqueous solution of tetrabutyl titanate ethanol, and the pH value was adjusted before the reaction was carried out to obtain aramid fibers deposited by nano-titanium dioxide sol gel. (B3) The aramid fibers deposited by nano-titanium dioxide sol gel obtained in step (B2) are immersed in an aqueous solution of terminal amino hyperbranched polyamide in ethanol for reaction. Through multiple chemical reactions between the terminal amino groups of the hyperbranched polyamide and the hydroxyl groups on the surface of nano-titanium dioxide and the hydroxyl ester groups of the polydopamine layer, a cross-linked reinforced structure is formed, and the modified aramid fibers are obtained.

[0027] In some specific embodiments, the molar concentration of the tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution in step (B1) is 0.06~0.1 mol / L (e.g., 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L or 0.1 mol / L, etc.), and the pH value is 8~9 (e.g., 8, 8.2, 8.4, 8.6, 8.8 or 9, etc.).

[0028] In some specific embodiments, the amount of the tris(hydroxymethyl)aminomethane hydrochloric acid buffer solution used in step (B1) is 10 to 30 times the mass of the aramid fiber, for example, 10 times, 15 times, 20 times, 25 times or 30 times.

[0029] In some specific embodiments, the mass of the dopamine hydrochloride is 1-3%, for example, 1%, 1.5%, 2%, 2.5% or 3%, based on the mass of the tris(hydroxymethyl)aminomethane hydrochloride buffer solution in step (B1) being 100%.

[0030] In some specific embodiments, the mass of the dopamine hydrochloride in step (B1) is 3 to 5% of the industrial fiber, such as 3%, 3.2%, 3.5%, 4%, 4.2%, 4.5% or 5%.

[0031] In some specific embodiments, the linear density of the aramid fiber in step (B1) is 140~450 dtex, such as 145 dtex, 170 dtex, 190 dtex, 210 dtex, 230 dtex, 250 dtex, 270 dtex, 290 dtex, 330 dtex, 350 dtex, 380 dtex or 420 dtex.

[0032] In some specific embodiments, the temperature of the reaction in step (B1) is 20~40°C (e.g., 20°C, 25°C, 30°C, 35°C or 40°C, etc.), and the time is 12~24 h (e.g., 12 h, 15 h, 17 h, 19 h, 21 h, 23 h or 24 h, etc.).

[0033] In some specific embodiments, the amount of tetrabutyl titanate ethanol aqueous solution used in step (B2) is 10 to 20 times the mass of aramid fiber, for example, 10 times, 12 times, 14 times, 16 times, 18 times or 20 times.

[0034] In some specific embodiments, the volume ratio of ethanol to water in the tetrabutyl titanate ethanol aqueous solution in step (B2) is (3~5):1 (e.g., 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, etc.), and the mass percentage of tetrabutyl titanate is 5~15 (e.g., 5%, 7%, 9%, 11%, 13% or 15%, etc.).

[0035] In some specific embodiments, the pH value of the system after adjusting the pH value in step (B2) is 3 to 5, such as 3, 3.5, 4, 4.5 or 5.

[0036] In some specific embodiments, the reaction temperature in step (B2) is 30~50°C (e.g., 30°C, 32°C, 35°C, 38°C, 41°C, 43°C, 45°C, 48°C or 50°C, etc.), and the time is 2~4 h (e.g., 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.).

[0037] In some specific embodiments, the amount of the terminal amino hyperbranched polyamide ethanol aqueous solution used in step (B3) is 8 to 15 times the mass of the industrial fiber, for example, 8, 9, 10, 11, 12, 13, 14 or 15 times.

[0038] In some specific embodiments, the volume ratio of ethanol to water in the amino-terminated hyperbranched polyamide ethanol aqueous solution in step (B3) is (7~9):1 (e.g., 7:1, 7.5:1, 8:1, 8.5:1 or 9:1, etc.), and the mass percentage content of amino-terminated hyperbranched polyamide is 4~8% (e.g., 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%, etc.).

[0039] In some specific embodiments, the temperature of the reaction in step (B3) is 50~70°C (e.g., 50°C, 55°C, 60°C, 65°C or 70°C, etc.), and the time is 1~3 h (e.g., 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc.).

[0040] In some specific embodiments, the modified waterborne polyurethane dual-mode resin is prepared by waterborne polyurethane resin through segmental prepolymerization with castor oil-based polyol, double self-crosslinking with ketoxime isocyanate groups, and reinforcement with nanocellulose whiskers.

[0041] In this application, the modified waterborne polyurethane dual-mode resin is first introduced into a trifunctional branched crosslinking structure via castor oil-based polyols, constructing branching points in the waterborne polyurethane molecular chain, thus solving the problem of insufficient crosslinking sites and mechanical strength in conventional linear waterborne polyurethanes. Then, through ketoxime isocyanate-based dual self-crosslinking, an interpenetrating network structure is formed by the crosslinking of ketoxime and isocyanate groups. The dual crosslinking complements and synergistically enhances each other, significantly increasing the resin's crosslinking density and solving the problem of limited crosslinking degree and small improvement in mechanical properties in single crosslinking systems. Finally, nanocellulose whiskers are used for reinforcement treatment, uniformly dispersed in the resin matrix. The abundant hydroxyl groups on their surface form a dense hydrogen bond network with the polyurethane molecular chain, providing rigid framework reinforcement to the crosslinking network at the nanoscale. The synergistic effect of these three elements gives the resin high crosslinking density, high toughness, and high strength, overcoming the problems of high brittleness and poor impact resistance in existing waterborne polyurethane films. This allows the fabric to achieve efficient stress transfer and energy dissipation between the fibers and resin when under stress, improving the fabric's cut resistance.

[0042] In some specific embodiments, the modified waterborne polyurethane dual-mode resin is prepared by the following method, which includes the following steps: (C1) Waterborne polyurethane resin is mixed with castor oil, isophorone diisocyanate and catalyst are added first for prepolymerization reaction, and then hydrophilic chain extender is added for chain extension reaction to obtain castor oil modified waterborne polyurethane prepolymer. (C2) Add diacetone acrylamide to the castor oil modified waterborne polyurethane prepolymer obtained in step (C1) and react. The ketone carbonyl group of diacetone acrylamide introduces ketoxime crosslinking active sites on the prepolymer molecular chain. Then add adipic acid dihydrazide and react. The hydrazide group of adipic acid dihydrazide reacts with the ketoxime crosslinking active sites to form a hydrazone crosslinking network, realizing ketoxime crosslinking. Then add hexamethylene diisocyanate trimer and react. The isocyanate group of hexamethylene diisocyanate trimer reacts with the active hydrogen on the prepolymer molecular chain to form a urethane crosslinking network, realizing isocyanate group crosslinking. Thus, a double self-crosslinking network structure of ketoxime isocyanate group is formed inside the prepolymer. Then add triethylamine for neutralization. Finally, add water for emulsification and dispersion to obtain waterborne polyurethane emulsion. (C3) Add the aqueous suspension of nanocellulose whiskers to the aqueous polyurethane emulsion obtained in step (C2) and mix to obtain the modified aqueous polyurethane bimodal resin.

[0043] In some specific embodiments, the mass ratio of the waterborne polyurethane resin to castor oil in step (C1) is 1:(0.1~0.2), for example, 1:0.12, 1:0.14, 1:0.16 or 1:0.18, etc.

[0044] In some specific embodiments, after mixing in step (C1), the process further includes vacuum dehydration at 100~120℃ (e.g., 100℃, 105℃, 110℃, 115℃ or 120℃, etc.) for 1~2 h (e.g., 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h, etc.), followed by cooling to 70~80℃ (e.g., 70℃, 72℃, 74℃, 76℃, 78℃ or 80℃, etc.).

[0045] In some specific embodiments, the amount of isophorone diisocyanate added in step (C1) is 15-30% of the mass of the waterborne polyurethane resin, such as 17%, 19%, 21%, 23%, 25%, 27% or 29%.

[0046] In some specific embodiments, the catalyst in step (C1) is dibutyltin dilaurate.

[0047] In some specific embodiments, the amount of catalyst added in step (C1) is 0.05~0.15% of the waterborne polyurethane resin, such as 0.05%, 0.07%, 0.09%, 0.11%, 0.13% or 0.15%.

[0048] In some specific embodiments, the prepolymerization temperature in step (C1) is 75~85°C (e.g., 75°C, 77°C, 79°C, 81°C, 83°C or 85°C, etc.), and the time is 2~3 h (e.g., 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, etc.).

[0049] In some specific embodiments, the hydrophilic chain extender in step (C1) is dimethylolpropionic acid.

[0050] In some specific embodiments, the amount of hydrophilic chain extender added in step (C1) is 5 to 10% of the waterborne polyurethane resin, such as 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 9% or 10%.

[0051] In some specific embodiments, the chain extension reaction in step (C1) is carried out at a temperature of 75-85°C (e.g., 75°C, 77°C, 79°C, 81°C, 83°C or 85°C) and for a time of 1-2 h (e.g., 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h).

[0052] In some specific embodiments, the solid content of the waterborne polyurethane resin in step (C1) is 30-50%, such as 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, or 48%.

[0053] In this application, there are no special requirements for the type of waterborne polyurethane resin. Commercially available waterborne polyurethane resins can be selected, such as Anhui Dawei Huatai New Material Technology Co., Ltd. (Anhui Dawei Huatai) AH-1704-3, Jiangyin Moore Chemical New Material Co., Ltd. W-1930, Guangzhou Yuhang Environmental Protection Materials Co., Ltd. (Yudoli brand) PU-2890, etc.

[0054] In some specific embodiments, the mass ratio of the solid content of diacetone acrylamide to castor oil modified waterborne polyurethane prepolymer in step (C2) is 1:(20~30), for example, 1:20, 1:22, 1:24, 1:26, 1:28 or 1:30, etc.

[0055] In some specific embodiments, the reaction temperature for adding diacetone acrylamide in step (C2) is 50~60℃ (e.g., 50℃, 52℃, 54℃, 56℃, 58℃ or 60℃, etc.), and the time is 30~60 min (e.g., 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.).

[0056] In some specific embodiments, the molar ratio of adipic acid dihydrazide to diacetone acrylamide in step (C2) is (1~1.2):1, for example 1:1, 1.05:1, 1.1:1, 1.15:1 or 1.2:1, etc.

[0057] In some specific embodiments, the reaction temperature for adding adipic dihydrazide in step (C2) is 40~50℃ (e.g., 40℃, 42℃, 44℃, 46℃, 48℃ or 50℃, etc.), and the time is 20~40 min (e.g., 20 min, 25 min, 30 min, 35 min or 40 min, etc.).

[0058] In some specific embodiments, the mass ratio of the solid content of the hexamethylene diisocyanate trimer to the castor oil-modified waterborne polyurethane prepolymer in step (C2) is 1:(15~25), for example, 1:15, 1:17, 1:19, 1:21, 1:23 or 1:25, etc.

[0059] In some specific embodiments, the reaction temperature for adding hexamethylene diisocyanate trimer in step (C2) is 50-60°C (e.g., 50°C, 52°C, 54°C, 56°C, 58°C, or 60°C) and the time is 30-60 min (e.g., 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, or 60 min).

[0060] In some specific embodiments, the amount of triethylamine added in step (C2) is 0.9 to 1.1 times the molar amount of the hydrophilic chain extender, for example, 0.9 times, 0.95 times, 1 time, 1.05 times or 1.1 times.

[0061] In some specific embodiments, the neutralization temperature in step (C2) is 30~40°C (e.g., 30°C, 32°C, 34°C, 36°C, 38°C or 40°C, etc.), and the pH value after neutralization is 7.5~8.5 (e.g., 7.5, 7.7, 7.9, 8.1, 8.3 or 8.5, etc.).

[0062] In some specific embodiments, the mass percentage of nanocellulose whiskers in the aqueous suspension of nanocellulose whiskers in step (C3) is 1-5%, such as 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%.

[0063] In some specific embodiments, the mass ratio of the nanocellulose whiskers to the aqueous polyurethane resin in step (C3) is 1:(30~50), for example, 1:30, 1:35, 1:40, 1:45 or 1:50.

[0064] In some specific embodiments, the mixing described in step (C3) is performed under ultrasonic oscillation conditions, wherein the power of the ultrasonic oscillation is 200~400 W (e.g., 200 W, 250 W, 300 W, 350 W or 400 W, etc.) and the time is 10~30 min (e.g., 10 min, 15 min, 20 min, 25 min or 30 min, etc.).

[0065] In some specific embodiments, the surface layer has a plain weave structure.

[0066] In some specific embodiments, the inner layer has a twill weave structure.

[0067] In some specific embodiments, the splicing warp yarn is modified ultra-high molecular weight polyethylene fiber, which is the same type as the warp yarn.

[0068] In some specific embodiments, the mass ratio of the modified ultra-high molecular weight polyethylene fiber, the modified aramid fiber, and the modified waterborne polyurethane bimodal resin is (45~65):(25~45):(5~15), for example, 45:25:5, 50:30:7, 55:35:9, 60:40:12, or 65:45:15, etc.

[0069] In some specific embodiments, the mass percentage of modified waterborne polyurethane dual-mode resin in the aqueous dispersion of the modified waterborne polyurethane dual-mode resin is 5-15%, such as 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, or 15%.

[0070] Secondly, this application provides a method for preparing a double-layered cut-resistant fabric as described in the first aspect. The preparation method includes the following steps: (1) Modified ultra-high molecular weight polyethylene fiber is used as warp yarn and modified aramid fiber is used as weft yarn, and they are respectively wound, warped and sized. (2) The fabric is woven using a double-beam air-jet loom, with the outer and inner layers connected by splicing warp yarns to form a double-layered fabric. (3) The obtained double-layer fabric is immersed in an aqueous solution containing desizing enzyme and scouring agent for desizing treatment. After washing and drying, it is then immersed in an aqueous dispersion containing modified waterborne polyurethane double-mode resin for padding treatment. (4) The impregnated double-layer fabric is pre-dried and baked, and then shaped to obtain the cut-resistant double-layer fabric.

[0071] In some specific embodiments, the weaving speed in step (2) is 300~500 rpm, such as 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm.

[0072] In some specific embodiments, the warp density of the double-layer fabric in step (2) is 180 to 220 yarns / inch, such as 180 yarns / inch, 185 yarns / inch, 190 yarns / inch, 195 yarns / inch, 200 yarns / inch, 205 yarns / inch, 210 yarns / inch or 220 yarns / inch, etc.

[0073] In some specific embodiments, the weft density of the double-layer fabric in step (2) is 160 to 200 yarns / inch, such as 160 yarns / inch, 170 yarns / inch, 180 yarns / inch, 190 yarns / inch or 200 yarns / inch.

[0074] In some specific embodiments, the desizing enzyme in step (3) includes α-amylase.

[0075] In some specific embodiments, the mass percentage of desizing enzyme in the aqueous solution in step (3) is 0.1-1%, for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%.

[0076] In some specific embodiments, the refining agent in step (3) includes a compound of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of (2~3):1 (e.g., 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3:1, etc.).

[0077] In some specific embodiments, the mass percentage of the refining agent in the aqueous solution in step (3) is 1~3%, for example 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6% or 2.8%, etc.

[0078] In some specific embodiments, the temperature of the desizing treatment in step (3) is 80~95℃ (e.g., 80℃, 82℃, 84℃, 86℃, 88℃, 90℃, 92℃ or 94℃, etc.), and the time is 30~60 min (e.g., 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.).

[0079] In some specific embodiments, the immersion rolling process in step (3) is a two-immersion and two-roll process.

[0080] In some specific embodiments, the rolling residue of the impregnation process in step (3) is 70-85%, such as 70%, 72%, 74%, 76%, 78%, 80%, 81%, 83% or 85%.

[0081] In some specific embodiments, the pre-baking temperature in step (4) is 80~100℃ (e.g., 80℃, 85℃, 90℃, 95℃ or 100℃, etc.), and the time is 1~3 min (e.g., 1 min, 1.5 min, 2 min, 2.5 min or 3 min, etc.).

[0082] In some specific embodiments, the baking temperature in step (4) is 150~180℃ (e.g., 150℃, 155℃, 160℃, 165℃, 170℃, 175℃ or 180℃, etc.), and the time is 2~4 min (e.g., 2 min, 2.5 min, 3 min, 3.5 min or 4 min, etc.).

[0083] In some specific embodiments, the shaping temperature in step (4) is 120~150℃ (e.g., 120℃, 125℃, 130℃, 135℃, 140℃, 145℃ or 150℃, etc.), and the time is 3~5 min (e.g., 3 min, 3.5 min, 4 min, 4.5 min or 5 min, etc.).

[0084] Thirdly, this application provides a textile product comprising the cut-resistant fabric described in the first aspect.

[0085] Compared with the prior art, this application has the following advantages: The cut-resistant fabric provided in this application maintains the original high strength and excellent cut resistance of the fiber while being able to form a long-lasting and stable interfacial chemical bond with the waterborne polyurethane film, making it difficult to peel off. Furthermore, the modified waterborne polyurethane bimodal resin used has high crosslinking density, high toughness, and high strength, enabling the fabric to achieve efficient stress transfer and energy dissipation between the fiber and the resin when under stress. This results in the fabric having excellent cut resistance, high tensile strength, and high tear strength. Detailed Implementation

[0086] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0087] Preparation Example 1-1 A modified ultra-high molecular weight polyethylene fiber, the preparation method of which includes the following steps: (1) Place ultra-high molecular weight polyethylene fiber (linear density of 150 dtex) in a plasma treatment device and perform plasma surface activation treatment in a mixed atmosphere of oxygen and argon. At 20°C, treat with a power of 150 W for 4 min to obtain surface-activated ultra-high molecular weight polyethylene fiber. (2) The surface-activated ultra-high molecular weight polyethylene fiber was immersed in an aqueous solution of acrylamide with a mass percentage of 5% and grafted copolymerized at 35°C for 1 h to obtain acrylamide grafted copolymerized ultra-high molecular weight polyethylene fiber. (3) The acrylamide graft copolymerized ultra-high molecular weight polyethylene fiber was immersed in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride and chitosan, and reacted at 20°C for 12 h. After being taken out, it was washed and dried to obtain modified ultra-high molecular weight polyethylene fiber. The acrylamide aqueous solution was added at 8% of the mass of the ultra-high molecular weight polyethylene fiber; the trimethylolaminomethane hydrochloric acid buffer solution had a molar concentration of 0.06 mol / L and a pH of 8.0, and was added at 10 times the mass of the ultra-high molecular weight polyethylene fiber; the mass fraction of dopamine hydrochloride in the trimethylolaminomethane hydrochloric acid buffer solution was 1%; and the mass fraction of chitosan in the trimethylolaminomethane hydrochloric acid buffer solution was 1%.

[0088] Preparation Examples 1-2 A modified ultra-high molecular weight polyethylene fiber, the preparation method of which includes the following steps: (1) Place ultra-high molecular weight polyethylene fiber (linear density of 330 dtex) in a plasma treatment device and perform plasma surface activation treatment in a mixed atmosphere of oxygen and argon. At 30°C, treat with a power of 200 W for 6 min to obtain surface-activated ultra-high molecular weight polyethylene fiber. (2) The surface-activated ultra-high molecular weight polyethylene fiber was immersed in an aqueous solution of acrylamide with a mass percentage of 7.5% and grafted copolymerized at 42°C for 2 h to obtain acrylamide grafted copolymerized ultra-high molecular weight polyethylene fiber. (3) The acrylamide graft copolymerized ultra-high molecular weight polyethylene fiber was immersed in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride and chitosan, and reacted at 30°C for 18 h. After being taken out, it was washed and dried to obtain modified ultra-high molecular weight polyethylene fiber. The acrylamide aqueous solution was added at 11.5% of the mass of the ultra-high molecular weight polyethylene fiber; the trimethylolaminomethane hydrochloric acid buffer solution had a molar concentration of 0.08 mol / L and a pH of 8.5, and was added at 20 times the mass of the ultra-high molecular weight polyethylene fiber; the dopamine hydrochloride was added at 2% by mass in the trimethylolaminomethane hydrochloric acid buffer solution; and the chitosan was added at 1.5% by mass in the trimethylolaminomethane hydrochloric acid buffer solution.

[0089] Preparation Examples 1-3 A modified ultra-high molecular weight polyethylene fiber, the preparation method of which includes the following steps: (1) Place ultra-high molecular weight polyethylene fiber (linear density of 330 dtex) in a plasma treatment device and perform plasma surface activation treatment in a mixed atmosphere of oxygen and argon. At 40°C, treat with a power of 250 W for 8 min to obtain surface-activated ultra-high molecular weight polyethylene fiber. (2) The surface-activated ultra-high molecular weight polyethylene fiber was immersed in an aqueous solution of acrylamide with a mass percentage of 10% and grafted copolymerized at 50°C for 3 h to obtain acrylamide grafted copolymerized ultra-high molecular weight polyethylene fiber. (3) The acrylamide graft copolymerized ultra-high molecular weight polyethylene fiber was immersed in a trihydroxymethylaminomethane hydrochloride buffer solution containing dopamine hydrochloride and chitosan and reacted at 40°C for 24 h. After being taken out, it was washed and dried to obtain modified ultra-high molecular weight polyethylene fiber. The acrylamide aqueous solution was added at 15% of the mass of the ultra-high molecular weight polyethylene fiber; the trimethylolaminomethane hydrochloric acid buffer solution had a molar concentration of 0.1 mol / L and a pH of 9.0, and was added at 30 times the mass of the ultra-high molecular weight polyethylene fiber; the dopamine hydrochloride was added at 3% of the mass of the trimethylolaminomethane hydrochloric acid buffer solution; and the chitosan was added at 2% of the mass of the trimethylolaminomethane hydrochloric acid buffer solution.

[0090] Preparation Example 2-1 A modified aramid fiber, the preparation method of which includes the following steps: (1) Immerse aramid fibers (linear density of 145 dtex) in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride and stir at 20°C for 12 h to form a polydopamine coating layer on the fiber surface. (2) After the reaction is complete, the aramid fiber coated with polydopamine is immersed in a tetrabutyl titanate ethanol aqueous solution with a mass of 10 times that of the aramid fiber, and glacial acetic acid is added to adjust the pH to 3.0. The reaction is carried out at 30°C for 2 h to deposit nano-titanium dioxide particles on the surface of the polydopamine layer. (3) After the reaction is completed, the aramid fiber with nano-titanium dioxide particles deposited on the surface is immersed in an aqueous solution of terminal amino hyperbranched polyamide ethanol, which is 8 times the mass of the aramid fiber, and reacted at 50°C for 1 h. After being taken out, it is washed and dried to obtain the modified aramid fiber. The concentration of the trimethylolaminomethane hydrochloric acid buffer solution was 0.06 mol / L, the pH was 8, and the amount used was 10 times the mass of the aramid fiber. The mass fraction of dopamine hydrochloride in the trimethylolaminomethane hydrochloric acid buffer solution was 1%. The volume ratio of ethanol to water in the tetrabutyl titanate ethanol aqueous solution was 3:1, and the mass fraction of tetrabutyl titanate was 5%. The volume ratio of ethanol to water in the terminal amino hyperbranched polyamide ethanol aqueous solution was 7:1, and the mass fraction of terminal amino hyperbranched polyamide was 4%.

[0091] Preparation Example 2-2 A modified aramid fiber, the preparation method of which includes the following steps: (1) Immerse aramid fibers (linear density of 220 dtex) in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride and stir at 30°C for 18 h to form a polydopamine coating layer on the fiber surface. (2) After the reaction is complete, the aramid fiber coated with polydopamine is immersed in a tetrabutyl titanate ethanol aqueous solution with a mass of 15 times that of the aramid fiber, and glacial acetic acid is added to adjust the pH to 4.0. The reaction is carried out at 40°C for 3 h to deposit nano-titanium dioxide particles on the surface of the polydopamine layer. (3) After the reaction is completed, the aramid fiber with nano-titanium dioxide particles deposited on the surface is immersed in an aqueous solution of terminal amino hyperbranched polyamide ethanol with a mass of 11 times that of the aramid fiber and reacted at 60°C for 2 h. After being taken out, it is washed and dried to obtain the modified aramid fiber. The concentration of the trimethylolaminomethane hydrochloric acid buffer solution was 0.08 mol / L, the pH was 8.5, and the amount used was 20 times the mass of the aramid fiber. The mass fraction of dopamine hydrochloride in the trimethylolaminomethane hydrochloric acid buffer solution was 2%. The volume ratio of ethanol to water in the tetrabutyl titanate ethanol aqueous solution was 4:1, and the mass fraction of tetrabutyl titanate was 10%. The volume ratio of ethanol to water in the terminal amino hyperbranched polyamide ethanol aqueous solution was 8:1, and the mass fraction of terminal amino hyperbranched polyamide was 6%.

[0092] Preparation Examples 2-3 A modified aramid fiber, the preparation method of which includes the following steps: (1) Immerse aramid fibers (linear density of 440 dtex) in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride and stir at 40°C for 24 h to form a polydopamine coating layer on the fiber surface. (2) After the reaction is complete, the aramid fiber coated with polydopamine is immersed in an aqueous solution of tetrabutyl titanate ethanol, which is 20 times the weight of the aramid fiber. Glacial acetic acid is added to adjust the pH to 5.0, and the reaction is carried out at 50°C for 4 h to deposit nano-titanium dioxide particles on the surface of the polydopamine layer. (3) After the reaction is completed, the aramid fiber with nano-titanium dioxide particles deposited on the surface is immersed in an aqueous solution of terminal amino hyperbranched polyamide ethanol, which is 8 times the mass of the aramid fiber, and reacted at 70°C for 3 h. After being taken out, it is washed and dried to obtain the modified aramid fiber. The concentration of the trimethylolaminomethane hydrochloric acid buffer solution was 0.1 mol / L, the pH was 9.0, and the amount used was 30 times the mass of the aramid fiber. The mass fraction of dopamine hydrochloride in the trimethylolaminomethane hydrochloric acid buffer solution was 3%. The volume ratio of ethanol to water in the tetrabutyl titanate ethanol aqueous solution was 5:1, and the mass fraction of tetrabutyl titanate was 15%. The volume ratio of ethanol to water in the terminal amino hyperbranched polyamide ethanol aqueous solution was 9:1, and the mass fraction of terminal amino hyperbranched polyamide was 8%.

[0093] Preparation Example 3-1 A modified waterborne polyurethane dual-mode resin, the preparation method of which includes the following steps: (1) Aqueous polyurethane resin (solid content of 30%, Anhui Dawei Huatai AH-1704-3 (nonionic aqueous PU dispersion)) was mixed with castor oil, vacuum dehydrated at 100℃ for 1 h, cooled to 70℃ and then added isophorone diisocyanate and dibutyltin dilaurate, and prepolymerized at 75℃ for 2 h, then added dimethylolpropionic acid and continued to react for 1 h to obtain castor oil modified aqueous polyurethane prepolymer; (2) Cool the castor oil-modified waterborne polyurethane prepolymer to 50°C, add diacetone acrylamide, stir and react for 30 min, cool to 40°C, add adipate dihydrazide, stir and react for 20 min, add hexamethylene diisocyanate trimer, react at 50°C for 30 min, cool to 30°C, add triethylamine to neutralize to pH 7.5, add deionized water under high speed stirring for emulsification and dispersion, and obtain waterborne polyurethane emulsion; (3) The nanocellulose whisker aqueous suspension was added to the waterborne polyurethane emulsion by stirring and ultrasonic oscillation. The ultrasonic oscillation power was 200 W and the time was 10 min to obtain the modified waterborne polyurethane bimodal resin. The composition of the aqueous polyurethane resin and castor oil is as follows: mass ratio 1:0.1; mass ratio 1:0.15; dibutyltin dilaurate is added at 0.05% of the mass of the aqueous polyurethane resin; dimethylolpropionic acid is added at 5% of the mass of the aqueous polyurethane resin; mass ratio 1:20 of the solid content of diacetone acrylamide and castor oil-modified aqueous polyurethane prepolymer; molar ratio 1:1 of adipic acid dihydrazide and diacetone acrylamide; mass ratio 1:15 of the solid content of hexamethylene diisocyanate trimer and castor oil-modified aqueous polyurethane prepolymer; triethylamine is added at 0.9 times the molar amount of dimethylolpropionic acid; the mass percentage of nanocellulose whiskers in the nanocellulose whisker aqueous suspension is 1%; and the mass ratio of nanocellulose whiskers to aqueous polyurethane resin is 1:30.

[0094] Preparation Example 3-2 A modified waterborne polyurethane dual-mode resin, the preparation method of which includes the following steps: (1) A waterborne polyurethane resin (solid content of 30%, Jiangyin Moore W-1930 (anionic waterborne PU dispersion)) was mixed with castor oil, vacuum dehydrated at 110℃ for 1.5 h, cooled to 75℃ and then added isophorone diisocyanate and dibutyltin dilaurate. The mixture was prepolymerized at 80℃ for 2.5 h, and then dimethylolpropionic acid was added and the reaction was continued for 1.5 h to obtain castor oil modified waterborne polyurethane prepolymer. (2) Cool the castor oil-modified waterborne polyurethane prepolymer to 55°C, add diacetone acrylamide, stir and react for 45 min, cool to 45°C, add adipate dihydrazide, stir and react for 30 min, add hexamethylene diisocyanate trimer, react at 55°C for 45 min, cool to 35°C, add triethylamine to neutralize to pH 8.0, add deionized water under high speed stirring to emulsify and disperse, and obtain waterborne polyurethane emulsion; (3) The nanocellulose whisker aqueous suspension was added to the waterborne polyurethane emulsion by stirring and ultrasonic oscillation. The ultrasonic oscillation power was 300 W and the time was 20 min to obtain the modified waterborne polyurethane bimodal resin. The composition of the aqueous polyurethane resin and castor oil is as follows: mass ratio 1:0.15; mass ratio 1:0.22; dibutyltin dilaurate is added at 0.1% of the mass of the aqueous polyurethane resin; dimethylolpropionic acid is added at 7.5% of the mass of the aqueous polyurethane resin; mass ratio 1:25 of the solid content of diacetone acrylamide and castor oil-modified aqueous polyurethane prepolymer; molar ratio 1.1:1 of adipate dihydrazide and diacetone acrylamide; mass ratio 1:20 of the solid content of hexamethylene diisocyanate trimer and castor oil-modified aqueous polyurethane prepolymer; triethylamine is added at 1 times the molar amount of dimethylolpropionic acid; the mass percentage of nanocellulose whiskers in the nanocellulose whisker aqueous suspension is 3%; and the mass ratio of nanocellulose whiskers to aqueous polyurethane resin is 1:40.

[0095] Preparation Example 3-3 A modified waterborne polyurethane dual-mode resin, the preparation method of which includes the following steps: (1) Aqueous polyurethane resin (solid content of 30%, Jiangyin Moore W-1930 (anionic aqueous PU dispersion)) was mixed with castor oil and vacuum dehydrated at 120℃ for 2 h. After cooling to 80℃, isophorone diisocyanate was added, followed by dibutyltin dilaurate. The mixture was prepolymerized at 85℃ for 3 h, and then dimethylolpropionic acid was added. The reaction was continued for 2 h to obtain castor oil modified aqueous polyurethane prepolymer. (2) Cool the castor oil-modified waterborne polyurethane prepolymer to 60°C, add diacetone acrylamide, stir and react for 60 min, cool to 50°C, add adipate dihydrazide, stir and react for 40 min, add hexamethylene diisocyanate trimer, react at 60°C for 60 min, cool to 40°C, add triethylamine to neutralize to pH 8.5, add deionized water under high speed stirring for emulsification and dispersion, and obtain waterborne polyurethane emulsion; (3) The nanocellulose whisker aqueous suspension was added to the waterborne polyurethane emulsion by stirring and ultrasonic oscillation. The ultrasonic oscillation power was 400 W and the time was 30 min to obtain the modified waterborne polyurethane bimodal resin. The composition of the aqueous polyurethane resin and castor oil is as follows: mass ratio 1:0.2; mass ratio 1:0.3; dibutyltin dilaurate is added at 0.15% of the mass of the aqueous polyurethane resin; dimethylolpropionic acid is added at 10% of the mass of the aqueous polyurethane resin; mass ratio 1:30 of the solid content of diacetone acrylamide and castor oil-modified aqueous polyurethane prepolymer; molar ratio 1.2:1 of adipate dihydrazide and diacetone acrylamide; mass ratio 1:25 of the solid content of hexamethylene diisocyanate trimer and castor oil-modified aqueous polyurethane prepolymer; triethylamine is added at 1.1 times the molar amount of dimethylolpropionic acid; the mass percentage of nanocellulose whiskers in the nanocellulose whisker aqueous suspension is 5%; and the mass ratio of nanocellulose whiskers to aqueous polyurethane resin is 1:50.

[0096] Example 1 A double-layered cut-resistant fabric includes a greige fabric and an aqueous polyurethane film covering the surface of the greige fabric; The fabric comprises a surface layer and an inner layer, which are connected by splicing warp yarns. The warp yarns of both the surface and inner layers are modified ultra-high molecular weight polyethylene fibers (Preparation Example 1-1), and the weft yarns of both the surface and inner layers are modified aramid fibers (Preparation Example 2-1). The splicing warp yarns are modified ultra-high molecular weight polyethylene fibers (Preparation Example 1-1). The material of the waterborne polyurethane film includes modified waterborne polyurethane bimodal resin (Preparation Example 3-1). The method for preparing the cut-resistant fabric provided in this embodiment includes the following steps: (1) The warp and weft yarns are wound, warped, and sized respectively; (2) The fabric is woven using a double-shaft air-jet loom. The outer layer is plain weave and the inner layer is twill weave. The outer and inner layers are connected by splicing warp yarns to form a high-density double-layer fabric. The weaving speed is 300 rpm, the warp density is 180 ends / inch, and the weft density is 160 ends / inch. (3) The obtained high-density bilayer fabric was immersed in an aqueous solution containing α-amylase and scouring agent (a compound of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of 2:1), wherein the mass percentage of α-amylase in the aqueous solution was 0.5% and the mass percentage of scouring agent in the aqueous solution was 2%, and the fabric was treated at 80°C for 30 min, then washed and dried, and then immersed in an aqueous dispersion containing 5% by mass of modified waterborne polyurethane bilayer resin, for two dips and two nips, with a nip-out rate of 70%; (4) The impregnated fabric is pre-dried at 80°C for 1 min, then baked at 150°C for 2 min, and finally dried and set at 120°C for 3 min to obtain a double-layered cut-resistant fabric.

[0097] Example 2 A double-layered cut-resistant fabric includes a greige fabric and an aqueous polyurethane film covering the surface of the greige fabric; The fabric comprises a surface layer and an inner layer, which are connected vertically by bonding warp yarns. The warp yarns of both the surface and inner layers are modified ultra-high molecular weight polyethylene fibers (Preparation Examples 1-2), and the weft yarns of both the surface and inner layers are modified aramid fibers (Preparation Examples 2-2). The bonding warp yarns are modified ultra-high molecular weight polyethylene fibers (Preparation Examples 1-2). The material of the waterborne polyurethane film includes modified waterborne polyurethane bimodal resin (Preparation Examples 3-2). The method for preparing the cut-resistant fabric provided in this embodiment includes the following steps: (1) The warp and weft yarns are wound, warped, and sized respectively; (2) The fabric is woven using a double-shaft air-jet loom. The outer layer is plain weave and the inner layer is twill weave. The outer and inner layers are connected by splicing warp yarns to form a high-density double-layer fabric. The weaving speed is 400 rpm, the warp density is 200 yarns / inch, and the weft density is 180 yarns / inch. (3) The obtained high-density bilayer fabric was immersed in an aqueous solution containing α-amylase and scouring agent (a compound of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of 2.5:1), wherein the mass percentage of α-amylase in the aqueous solution was 0.7% and the mass percentage of scouring agent in the aqueous solution was 2.5%, and treated at 87°C for 45 min. Then it was washed with water, dried, and then immersed in an aqueous dispersion containing 10% by mass of modified waterborne polyurethane bilayer resin. The mixture was dipped and rubbed twice, with a roll-off rate of 77%. (4) The impregnated fabric is pre-dried at 90°C for 2 min, then baked at 165°C for 3 min, and finally dried and set at 135°C for 4 min to obtain a double-layered cut-resistant fabric.

[0098] Example 3 A double-layered cut-resistant fabric includes a greige fabric and an aqueous polyurethane film covering the surface of the greige fabric; The fabric comprises a surface layer and an inner layer, which are connected by splicing warp yarns. The warp yarns of both the surface and inner layers are modified ultra-high molecular weight polyethylene fibers (Preparation Examples 1-3), and the weft yarns of both the surface and inner layers are modified aramid fibers (Preparation Examples 2-3). The splicing warp yarns are modified ultra-high molecular weight polyethylene fibers (Preparation Examples 1-3). The material of the waterborne polyurethane film includes modified waterborne polyurethane bimodal resin (Preparation Examples 3-3). The method for preparing the cut-resistant fabric provided in this embodiment includes the following steps: (1) The warp and weft yarns are wound, warped, and sized respectively; (2) The fabric is woven using a double-shaft air-jet loom. The outer layer is plain weave and the inner layer is twill weave. The outer and inner layers are connected by splicing warp yarns to form a high-density double-layer fabric. The weaving speed is 500 rpm, the warp density is 220 yarns / inch, and the weft density is 200 yarns / inch. (3) The obtained high-density bilayer fabric was immersed in an aqueous solution containing α-amylase and scouring agent (a compound of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of 3:1), wherein the mass percentage of α-amylase in the aqueous solution was 1% and the mass percentage of scouring agent in the aqueous solution was 3%, and the fabric was treated at 95°C for 60 min, then washed and dried, and then immersed in an aqueous dispersion containing 15% by mass of modified waterborne polyurethane bilayer resin, for two dips and two nips, with a nip-out rate of 85%; (4) The impregnated fabric is pre-dried at 100°C for 3 min, then baked at 180°C for 4 min, and finally dried and set at 150°C for 5 min to obtain a double-layered cut-resistant fabric.

[0099] Comparative Example 1 A double-layered cut-resistant fabric, which differs from Example 1 in that unmodified ultra-high molecular weight polyethylene fiber is used instead of the modified ultra-high molecular weight polyethylene fiber provided in Preparation Example 1-1, while other materials, structures and preparation methods are the same as in Example 1.

[0100] Comparative Example 2 A double-layered cut-resistant fabric, which differs from Example 1 in that unmodified aramid fibers are used to replace the modified aramid fibers provided in Preparation Example 2-1, while other materials, structures and preparation methods are the same as in Example 1.

[0101] Comparative Example 3 A double-layered cut-resistant fabric, which differs from Example 1 in that a waterborne polyurethane resin is used instead of the modified waterborne polyurethane dual-mode resin provided in Preparation Example 3-1, while other substances, structures and preparation methods are the same as in Example 1.

[0102] Comparative Example 4 A cut-resistant fabric includes a greige fabric and an aqueous polyurethane film covering the surface of the greige fabric; The fabric is woven from warp and weft yarns, the warp yarns are modified ultra-high molecular weight polyethylene fibers (Preparation Example 1-1), the weft yarns are modified aramid fibers (Preparation Example 2-1), and the material of the waterborne polyurethane film includes modified waterborne polyurethane bimodal resin (Preparation Example 3-1). The method for preparing the cut-resistant fabric provided in this comparative example includes the following steps: (1) The warp and weft yarns are wound, warped, and sized respectively; (2) The structure adopts plain weave, the weaving speed is 300 rpm, the warp density is 180 ends / inch, and the weft density is 160 ends / inch; (3) The fabric is immersed in an aqueous solution containing α-amylase and scouring agent (a compound of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of 2:1), wherein the mass percentage of α-amylase in the aqueous solution is 1% and the mass percentage of scouring agent in the aqueous solution is 3%, and is treated at 80°C for 30 min, then washed and dried, and then immersed in an aqueous dispersion containing 5% by mass of modified waterborne polyurethane double-mode resin, for two dips and two nips, with a nip-out rate of 70%; (4) The impregnated fabric is pre-dried at 80°C for 1 min, then baked at 150°C for 2 min, and finally dried and set at 120°C for 3 min to obtain the cut-resistant fabric.

[0103] Performance testing: (1) Cut resistance: Tested according to the method provided in EN 388:2016.

[0104] (2) Fracture strength: Tested according to the method provided in GB / T 3923.1-2013.

[0105] (3) Tear strength: Tested according to the method provided in GB / T 3917.2-2009.

[0106] The fabrics provided in Examples 1-3 and Comparative Examples 1-4 were tested according to the above test methods, and the test results are shown in Table 1: Table 1 According to the data in Table 1: The double-layer cut-resistant fabrics provided in Examples 1-3 have a cut resistance cycle of no less than 90 cycles, a tensile strength of no less than 2600 N, and a tear strength of no less than 380 N. They exhibit excellent cut resistance, high tensile strength, and high tear strength. Furthermore, from Example 1 to Example 3, the weight percentages of modified ultra-high molecular weight polyethylene fiber, modified aramid fiber, and modified waterborne polyurethane bimodal resin gradually increase. Simultaneously, the warp and weft densities of the fabric also increase. The synergistic enhancement effect among the three modified materials gradually increases with the optimization of the formulation. Therefore, the cut resistance, tensile strength, and tear strength all show a gradient upward trend.

[0107] Compared with Example 1, the fabric provided in Comparative Example 1 uses ultra-high molecular weight polyethylene fiber. Because its surface is highly crystalline and has no polar groups, it cannot form a strong interfacial chemical bond with the resin matrix. When subjected to force, the fiber is easily pulled out or slipped from the resin, so the number of cutting cycles and the breaking strength are significantly reduced.

[0108] Compared with Example 1, the fabric provided in Comparative Example 2 uses unmodified aramid fiber. Due to its smooth surface and lack of active groups, it also suffers from insufficient interfacial bonding and a significant decrease in the number of cutting cycles.

[0109] Compared with Example 1, the fabric provided in Comparative Example 3 uses unmodified waterborne polyurethane resin. Due to its linear molecular chain structure, low crosslinking density, and insufficient film toughness, it is prone to microcracks that propagate rapidly during dynamic cutting, making it unable to effectively transfer stress and significantly reducing the number of cutting cycles.

[0110] Compared with Example 1, the fabric provided in Comparative Example 4 uses a single-layer plain weave structure. The interlacing method of warp and weft yarns cannot form the fiber layer buffer in the double-layer structure, and the number of cutting cycles and breaking strength are significantly reduced.

[0111] In summary, for the cut-resistant fabric provided in this application, to achieve excellent cut resistance, high tensile strength, and high tear strength, there is a synergistic effect between the double-layer structure and the three modified materials, and none of them can be omitted.

[0112] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.

Claims

1. A double-layered cut-resistant fabric, characterized in that, The cut-resistant fabric includes a base fabric and an aqueous polyurethane film covering the surface of the base fabric. The fabric includes a surface layer and an inner layer, which are connected by splicing warp yarns. The warp yarns of the outer and inner layers are all modified ultra-high molecular weight polyethylene fibers, and the weft yarns of the outer and inner layers are all modified aramid fibers. The material of the waterborne polyurethane film includes a modified waterborne polyurethane dual-mode resin.

2. The cut-resistant fabric according to claim 1, characterized in that, The modified ultra-high molecular weight polyethylene fiber is prepared by plasma activation, acrylamide graft copolymerization, and polydopamine-chitosan composite coating treatment of ultra-high molecular weight polyethylene fiber. And / or, the modified aramid fiber is prepared by coating aramid fiber with dopamine hydrochloride self-polymerization, depositing nano-titanium dioxide sol-gel, and cross-linking and reinforcement treatment with amino-terminated hyperbranched polyamide; And / or, the modified waterborne polyurethane dual-mode resin is prepared by waterborne polyurethane resin through segmental prepolymerization with castor oil-based polyol, double self-crosslinking with ketoxime isocyanate, and reinforcement with nanocellulose whiskers.

3. The cut-resistant fabric according to claim 2, characterized in that, The modified ultra-high molecular weight polyethylene fiber is prepared by the following method, which includes the following steps: (A1) Ultra-high molecular weight polyethylene fibers were subjected to plasma surface activation treatment in a mixed atmosphere of oxygen and argon to obtain surface-activated ultra-high molecular weight polyethylene fibers. (A2) The surface-activated ultra-high molecular weight polyethylene fiber obtained in step (A1) is immersed in an aqueous solution of acrylamide to carry out a copolymerization reaction, thereby obtaining acrylamide graft copolymerized ultra-high molecular weight polyethylene fiber. (A3) The acrylamide graft copolymerized ultra-high molecular weight polyethylene fiber obtained in step (A2) is immersed in a trihydroxymethylaminomethane hydrochloride buffer solution containing dopamine hydrochloride and chitosan to react and obtain the modified ultra-high molecular weight polyethylene fiber. And / or, the modified aramid fiber is prepared by a method comprising the following steps: (B1) Aramid fibers are immersed in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine hydrochloride to react and obtain aramid fibers with dopamine hydrochloride self-polymerized surface coating. (B2) The aramid fibers coated with dopamine hydrochloride obtained in step (B1) were immersed in an aqueous solution of tetrabutyl titanate ethanol, and glacial acetic acid was added to adjust the pH value before the reaction was carried out to obtain aramid fibers deposited by nano-titanium dioxide sol gel. (B3) The aramid fibers deposited by nano-titanium dioxide sol gel obtained in step (B2) are immersed in an aqueous solution of amino-terminated hyperbranched polyamide ethanol to react and obtain the modified aramid fibers. And / or, the modified waterborne polyurethane dual-mode resin is prepared by the following method, the method comprising the following steps: (C1) Waterborne polyurethane resin is mixed with castor oil, isophorone diisocyanate and catalyst are added first for prepolymerization reaction, and then hydrophilic chain extender is added for chain extension reaction to obtain castor oil modified waterborne polyurethane prepolymer. (C2) Add diacetone acrylamide to the castor oil modified waterborne polyurethane prepolymer obtained in step (C1) and react, then add adipate dihydrazide and react, then add hexamethylene diisocyanate trimer and react, then add triethylamine for neutralization, and finally add water for emulsification and dispersion to obtain waterborne polyurethane emulsion. (C3) Add the aqueous suspension of nanocellulose whiskers to the aqueous polyurethane emulsion obtained in step (C2) and mix to obtain the modified aqueous polyurethane bimodal resin.

4. The cut-resistant fabric according to any one of claims 1 to 3, characterized in that, The surface layer has a plain weave structure; And / or, the inner layer has a twill weave structure.

5. The cut-resistant fabric according to any one of claims 1 to 4, characterized in that, The bonding warp yarn is modified ultra-high molecular weight polyethylene fiber; And / or, the mass ratio of the modified ultra-high molecular weight polyethylene fiber, the modified aramid fiber and the modified waterborne polyurethane dual-mode resin is (45~65):(25~45):(5~15); And / or, the mass percentage of the modified waterborne polyurethane dual-mode resin in the aqueous dispersion of the modified waterborne polyurethane dual-mode resin is 5-15%.

6. A method for preparing a double-layered, cut-resistant fabric as described in any one of claims 1 to 5, characterized in that, The preparation method includes the following steps: (1) Modified ultra-high molecular weight polyethylene fiber is used as warp yarn and modified aramid fiber is used as weft yarn, and they are respectively wound, warped and sized. (2) The fabric is woven using a double-beam air-jet loom, with the outer and inner layers connected by splicing warp yarns to form a double-layered fabric. (3) The obtained double-layer fabric is immersed in an aqueous solution containing desizing enzyme and scouring agent for desizing treatment. After washing and drying, it is then immersed in an aqueous dispersion containing modified waterborne polyurethane double-mode resin for padding treatment. (4) The impregnated double-layer fabric is pre-dried and baked, and then shaped to obtain the cut-resistant double-layer fabric.

7. The preparation method according to claim 6, characterized in that, The desizing enzyme in step (3) includes α-amylase; And / or, the refining agent in step (3) comprises a compound of fatty alcohol polyoxyethylene ether and sodium dodecylbenzene sulfonate in a mass ratio of (2~3):

1.

8. The preparation method according to claim 6 or 7, characterized in that, The desizing treatment in step (3) is performed at a temperature of 80~95℃ for 30~60 min. And / or, the immersion rolling process in step (3) is a two-dip two-roll process; And / or, the roll residue of the impregnation treatment in step (3) is 70-85%.

9. The preparation method according to any one of claims 6 to 8, characterized in that, The pre-baking temperature in step (4) is 80~100℃, and the time is 1~3 min; And / or, the baking temperature in step (4) is 150~180℃ and the time is 2~4 min; And / or, the shaping temperature in step (4) is 120~150℃ and the time is 3~5 min.

10. A textile product, characterized in that, The textile includes the cut-resistant fabric as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Puncture-resistant fabric for fencing clothes and preparation method of puncture-resistant fabric

    CN116254706A